CSP-1103 (CHF5074) stabilizes human transthyretin in healthy human subjects. (2nd January 2017) - Qiang, Lixia; Guan, Yanxia; Li, Xiangshun; Liu, Li; Mu, Yanshuang; Sugano, Aki; Takaoka, Yutaka; Sakaeda, Toshiyuki; Imbimbo, Bruno P.; Yamamura, Ken-Ichi; Jin, Shoude; Li, Zhenghua
Abstract: Hereditary amyloid polyneuropathy is a type of protein misfolding disease. Transthyretin (TTR) is a homotetrameric serum protein and TTR tetramer dissociation is the limiting step in amyloid fibril formation. Thus, prevention of TTR dissociation is a promising therapeutic approach and some TTR stabilizers have been approved for the treatment of TTR amyloidosis. CSP-1103 (CHF5074) is a non-steroidal anti-inflammatory derivative that lacks cyclooxygenase inhibitory activity. In vitro, CSP-1103 stabilizes the TTR tetramer by binding to the thyroxine (T4) binding site. We have previously shown that serum TTR levels were increased by oral CSP-1103 administration through stabilization of TTR tetramers in humanized mice at both the Ttr locus and the Rbp4 locus. To determine whether CSP-1103 stabilizes TTR tetramers in humans, multiple CSP-1103 oral doses were administered for two weeks to 48 healthy human volunteers in a double-blind, placebo-controlled, parallel-group study. CSP-1103 treatment stabilized TTR tetramers in a dose-dependent manner under normal or denaturing stress conditions, thereby increasing serum TTR levels. Preincubation of serum with CSP-1103 or diflunisal in vitro increased the TTR tetramer stability. Computer simulation analysis revealed that the binding affinities of CSP-1103 with TTR at pH 7.0 were similar to those of tafamidis, thus confirming that CSP-1103 has potent TTR-stabilizing activity.